The Construction of Black Manhood in Lorraine Hansberry's A Raisin in the Sun, From a Negative to a Positive Model: an eclectic theoretical perspective of Manhood - Saravia Vargas, José Roberto (2012)
tesis de maestría -- Universidad de Costa Rica. Programa de Estudios de Posgrado en Literatura. Maestría Académica en Literatura Inglesa, 2012